Clinical pharmacy in Ukraine according to the healthcare professionals' assessment - Andriy Zimenkovsky; Yuliya Nastyukha; Kateryna Kostyana; Oleg Devinyak; Marta Zayats; Andriy Koval; Oksana Denysiuk; Oksana Gorodnycha; Vitaliy Siatynia (Pensoft Publishers, 2019)
An anonymous questionnaire survey among healthcare professionals in Ukraine (n = 10737) showed contradictions in the attitude to the peculiarities of clinical pharmacy compared to a general pharmacy, the relation to the specialists who provide clinical pharmacy services, and the healthcare settings for them. The respondents considered the activity of clinical pharmacist necessary in 74.2%. The community pharmacies were identified as prior professional settings for clinical pharmacists in 55.3%; hospitals - 47.7%, hospital pharmacies - 45.0%. Among the directions of the clinical pharmacist's activity at the hospital, monitoring of drug safety and efficacy was stated by 69.9%, provision of the pharmaceutical care - 50.5%, evaluation of pharmacotherapy - 42.1%, processing of the local drug formulary - 26.8%. The respondents saw prospects for the development of clinical pharmacy in Ukraine in 54.2%. Therefore, there were differences in views on the key issues of clinical pharmacy throughout Ukraine and the insufficient support for its prospects.